2003
DOI: 10.1002/dc.10303
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of atypical squamous cells, cannot exclude a high‐grade squamous intraepithelial lesion (ASC‐H) on cervical samples: Is it significant?

Abstract: "Atypical squamous cells, cannot exclude a high-grade squamous intraepithelial lesion (ASC-H)" is a new diagnostic category in the 2001 Bethesda nomenclature system for cervical cytology. The purpose of this 7-mo retrospective study (March 1, 2002-September 30, 2002) was to evaluate the significance of ASC-H on cervical Thin Prep Pap Tests. During this period, 25 (0.27%) of 9,214 Pap Tests were diagnosed as ASC-H, 22 of which resulted in either follow-up cervical biopsies and/or cervical cones, and which forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
47
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 13 publications
7
47
0
4
Order By: Relevance
“…18 This is consistent with the results obtained from the majority of the studies observed, which demonstrated CIN II+ prevalences of more than 40%, according to the biopsy results. 3,5,6,[17][18][19][20][21][22][23][24]29 Our results confirmed that at the time of the first ASC-H report, immediate intervention with colposcopy was necessary, followed by a biopsy. This validates the medical management of ASC-H that is required by the "management algorithm from the time of the first atypical Pap, " which is included in the Chilean Ministry of Health's Clinical Guidelines for Cervical Cancer.…”
Section: Asc-h Issupporting
confidence: 72%
“…18 This is consistent with the results obtained from the majority of the studies observed, which demonstrated CIN II+ prevalences of more than 40%, according to the biopsy results. 3,5,6,[17][18][19][20][21][22][23][24]29 Our results confirmed that at the time of the first ASC-H report, immediate intervention with colposcopy was necessary, followed by a biopsy. This validates the medical management of ASC-H that is required by the "management algorithm from the time of the first atypical Pap, " which is included in the Chilean Ministry of Health's Clinical Guidelines for Cervical Cancer.…”
Section: Asc-h Issupporting
confidence: 72%
“…These findings fall within the rate ranges reported in different studies (Table 4). The wide ranges of ASC-US (1.2-39%) and, to a lesser extent, ASC-H (0.06-2%) may be contributed to the Bethesda system applied for categorization of ASC into ASC-US and ASC-H and further subcategorization of ASC-US into reactive and neoplastic counterparts (NCI Bethesda System, 2001;Solomon et al, 2001Selvaggi, 2003Barcelos et al, 2011). In addition, the heterogeneous morphology and lack of well-defined criteria for both ASC-US and ASC-H reflected in their poor interobserver agreement between laboratories or even the variable experience of the microscopists may account for these differences (Saad et al, 2006;Chivukula and Shidham;CytrynI et al, 2009;Tewari and Chaudhary., 2010;Barcelos et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Being equivocal, the term ASC is categorized by The Bethesda System (TBS) 2001 into atypical squamous cells of undetermined significance (ASC-US) where the cytologic changes are suggestive of but, quantitatively or qualitatively, are insufficient for a definitive interpretation of squamous intraepithelial lesion (SIL) and into atypical squamous cells-cannot exclude high squamous intraepithelial lesion (ASC-H) where the atypical squamous cells exhibit some equivocal features suggestive of but not sufficient to call high squamous intraepithelial lesions (HSIL) (NCI Bethesda System, 2001;Selvaggi, 2003). In addition to the possible progression of ASC-US and ASC-H into HSIL or invasive malignancy, the link between these lesions and high risk-human papillomavirus (HR-HPV) creates…”
Section: Introductionmentioning
confidence: 99%
“…In the recent study by Kingnate et al (2014), incidence of CIN 2-3/AIS and invasive lesion was 10.5% and 2.6%, respectively. In the literature, almost all studies evaluating histopathologic results of ASC-H smears were reported from North America where the incidence of cervical cancer appears to be relatively low (Alli and Ali, 2003;Louro et al, 2003;Selvaggi, 2003;Liman et al, 2005;Barreth et al, 2006;Saad et al, 2006;Srodon et al, 2006;McHale et al, 2007). The rate of underlying high-grade cervical lesion varied widely from 10% to 80%, in which less than 3.5% were invasive lesion (Alli and Ali, 2003;Louro et al, 2003;Selvaggi, 2003;Liman et al, 2005;Barreth et al, 2006;Saad et al, 2006;Srodon et al, 2006;McHale et al, 2007).…”
Section: Atypical Squamous Cells Cannot Exclude High-grade Squamous mentioning
confidence: 99%